Optimalisasi Peralatan Inert Gas System untuk Pencegahan Terjadinya Ledakan Pada Tangki Minyak di Kapal Tanker - Khaeroman Khaeroman; Noviarianto Noviarianto; Ridwan Ridwan (Jurnal Maritim Polimarin, 2025)
Oil tankers are a type of vessel specifically designed to transport oil or its derivatives. One of the preventive safety measures employed on these ships is the inert gas system—a system that generates gas with low oxygen content to prevent explosions onboard. However, an increase in oxygen concentration in the inert gas is a common issue encountered, which makes optimizing the performance of the inert gas system a matter of serious concern. The methodology adopted in this research is descriptive qualitative, with the inert gas system aboard MT. NORDDOLPHIN serving as the primary research object. Data collection was carried out through several approaches, including direct field observation, interviews with relevant personnel, and a literature review of technical documents such as instruction manuals and standard operating procedures (SOP) available on the vessel. The study demonstrates that the rise in oxygen content in inert gas is caused by inadequate maintenance of the fuel oil control valve and a dirty main burner, which leads to an imbalance in the combustion ratio. The effort undertaken to keep the oxygen level below the threshold of 4% involves lowering the correction factor on the boiler. This adjustment increases the fuel supply during combustion, which in turn raises the carbon dioxide concentration and lowers the oxygen level in the inert gas